2014
DOI: 10.3386/w19964
|View full text |Cite
|
Sign up to set email alerts
|

Public Transit Bus Procurement: The Role of Energy Prices, Regulation and Federal Subsidies

Abstract: The U.S. public transit system represents a multi-billion dollar industry that provides essential transit services to millions of urban residents. We study the market for new transit buses that features a set of non-profit transit agencies purchasing buses primarily from a few domestic bus makers. Unlike private vehicles, the fuel economy of public buses is irresponsive to fuel price changes. To understand this finding, we build a model of bus fleet management decisions of local transit agencies that yields te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Remanufacturing the engine or transmission had a similar target of extending the life of a bus for at least 4-10 years [94]; however, with a significant portion of expenses, more maintenance-intensive activities later on. In this regard, considering new technologies, one must consider the location of the manufacturer [95], mostly because it is associated with easy-to-access and service maintenance. The reason above is mostly associated with the fleet replacement policy.…”
Section: Bus Fleet Asset Management (Bfam) Realmmentioning
confidence: 99%
“…Remanufacturing the engine or transmission had a similar target of extending the life of a bus for at least 4-10 years [94]; however, with a significant portion of expenses, more maintenance-intensive activities later on. In this regard, considering new technologies, one must consider the location of the manufacturer [95], mostly because it is associated with easy-to-access and service maintenance. The reason above is mostly associated with the fleet replacement policy.…”
Section: Bus Fleet Asset Management (Bfam) Realmmentioning
confidence: 99%
“…Li et al . [2015] found that U.S. bus purchases were insensitive to energy price changes because of federal ‘buy American’ programs and other regulations and tax incentives. In Figure , we plot the distribution of domestic and foreign light‐duty vehicles registered by buyer type from 2015 to 2016.…”
Section: Background and Datamentioning
confidence: 99%
“…Federal regulations and subsidy incentives may discourage government buyers from responding to energy price changes (Li et al . [2015]). Governments may have specific vehicle uses and requirements that limit their choices, also causing government and commercial fleet buyers to be insensitive to fuel cost changes.…”
Section: Introductionmentioning
confidence: 99%
“…Managerial decisions on capital and fleet procurement are less frequent relative to operating input decisions of labor, maintenance, and fuel. While Li, Kahn and Nickelsburg (2015) study the durable bus investment decision and its implications on energy efficiency for transit agencies, we focus on the labor input decisions and productivity under the influence of labor union rules.…”
Section: A Model Of Transit Service Provision and Privatizationmentioning
confidence: 99%
“…Diamond (2016) finds similar results in areas with inelastic housing supply. and the fuel needed to move the bus are traded on a national market (Kahn, Li and Nickelsburg 2015).…”
Section: Introductionmentioning
confidence: 99%